Antibacterial and antioxidant activities of methanolic leaf extract of Maerua crassifolia - Kingsley Chimsorom Ckilaka, Godwin Christian Akuodor, Joseph Linus Akpan, Emeka Daniel Ogiji, Chukwuemeka Okorie Eze, Basil Chukwuma Ezeokpo (Journal of Applied Pharmaceutical Science, 2015)
The objective of this study was to investigate the antibacterial and antioxidant activities of the methanol leaf extract of Maerua crassifolia, an important medicinal plant used in Nigeria. The antibacterial properties of the methanol extract were studied against clinically important bacteria viz; Staphylococcus aureus, Shigella spp., Salmonella typhi, Bacillus subtilis and Escherichia coli by disc diffusion method. The free radical scavenging potential of the extract was assessed by measuring its capability for scavenging 2, 2-diphenyl-1-picrylhydrazyl (DPPH) radical. The methanol leaf extract of Maerua crassifolia at the concentration of 12.5-150 µg/ml, showed significant activity against all the tested organisms. The observed antioxidant activity of the leaf extract suggests that the extract is a potential source of natural antioxidant and could be useful in the treatment of diseases.
Keywords: Maerua crassifolia, leaf extract, methanol, antibacterial agent, DPPH, antioxidant.